Care actions of the obstetric nurse in planned home birth: integrative literature review (Research, Society and Development, 2022)
Objective: To identify the national and international scientific evidence available in the literature about the care actions of nurse midwives in planned home births. Method: This is an integrative literature review, which took place in November and December 2020. Ten articles from original research, complete, in English, Portuguese and Spanish, were included in the time frame from 2011 to 2020. Results: It is evident that the articles evaluated discuss the history of childbirth and the obstetric nurse; the profile of women who choose planned home birth and the reasons for this choice; and on the practice of obstetric nursing in childbirth in a home environment and its outcomes. Final considerations: The findings indicate that home births, planned and assisted by qualified professionals, have good maternal and neonatal outcomes and the obstetric nurse is recognized by women as a professional who respects the role and individual aspects of women.